Representations of immigrants and refugees in US K-12 school-to-home correspondence: an exploratory corpus-assisted discourse study. Issue 2 (August 2017) - Berger, Cynthia; Friginal, Eric; Roberts, Jennifer
Abstract : This study details a comparative, corpus-based discourse analysis of corpora containing educational documents distributed to parents and guardians of K-12 children in public schools in the United States (US). The exploratory local corpus ( n =152, 934) contains parent-directed educational documents collected from four public schools in a city located in the south-eastern US with an unusually high percentage of foreign-born residents. The comparison corpus ( n =147, 796) contains parent-directed documents collected from a sampling of K-12 schools across the US. FollowingBaker et al . (2008), keyness and collocations were utilised as central theoretical notions and tools of analysis, in addition to a lexical sophistication comparison, in order to investigate text simplification across corpora. Results show that while the first corpus used labels for students that were superficially inclusive, English language learners themselves were discursively represented as outsiders facing barriers to inclusion that native-English speaking monolingual students do not face. Furthermore, the first corpus revealed an emphasis on identifying and categorising language learners so as to provide them with immediate services, while the non-geographically specific corpus focussed more on the long-term development of learners and on preparation for post-secondary education. We discuss the implications for language policy in public education and for policies related to K-12 school-to-home correspondence.